On 3-Dimensional Contact Metric Generalized (k,μ)-Space Forms - D. G. Prakasha; Shyamal Kumar Hui; Kakasab Mirji (International Journal of Mathematics and Mathematical Sciences)
The present paper deals with a study of 3-dimensional contact metric generalized (k,μ)-space forms. We obtained necessary and sufficient condition for a 3-dimensional contact metric generalized (k,μ)-space form with Qϕ=ϕQ to be of constant curvature. We also obtained some conditions of such space forms to be pseudosymmetric and ξ-projectively flat, respectively.